Free intracellular Mg(2+) concentration and inhibition of NMDA responses in cultured rat neurons - Li-Smerin, Yingying (Blackwell Science Inc, 2001)
1. Intracellular Mg(2+) (Mg(i)(2+)) blocks single-channel currents and modulates the gating kinetics of NMDA receptors. However, previous data suggested that Mg(i)(2+) inhibits whole-cell current less effectively than predicted from excised-patch measurements. We examined the basis of this discrepancy by testing three hypothetical explanations. 2. To test the first hypothesis, that control of free Mg(i)(2+) concentration ([Mg(2+)](i)) during whole-cell recording was inadequate, we measured [Mg(2+)](i) using mag-indo-1 microfluorometry. The [Mg(2+)](i) measured in cultured neurons during whole-cell recording was similar to the pipette [Mg(2+)] measured in vitro, suggesting that [Mg(2+)](i) was adequately controlled. 3. To test the second hypothesis, that open-channel block by Mg(i)(2+) was modified by patch excision, we characterised the effects of Mg(i)(2+) using cell-attached recordings. We found the affinity and voltage dependence of open-channel block by Mg(i)(2+) similar in cell-attached and outside-out patches. Thus, the difference between Mg(i)(2+) inhibition of whole-cell and of patch currents cannot be attributed to a difference in Mg(i)(2+) block of single-channel current. 4. The third hypothesis tested was that the effect of Mg(i)(2+) on channel gating was modified by patch excision. Results of cell-attached recording and modelling of whole-cell data suggest that the Mg(i)(2+)-induced stabilisation of the channel open state is four times weaker after patch excision than in intact cells. This differential effect of Mg(i)(2+) on channel gating explains why Mg(i)(2+) inhibits whole-cell NMDA responses less effectively than patch responses.